Occurrence and Timing of Complications of Crown-Fractures in Permanent Incisors: A Randomized Clinical Trial - Demir, Pinar (2021)
Objective: To investigate the complications of crown fractures that might occur in different follow-up periods. Material and Methods: Individuals within the 6-13 age range with crown fracture and consulted to University Hospital were included in the study. Patients were randomly divided into three groups by block randomization method and evaluated clinical and radiographically for complications at the 6, 8 weeks, and 6, 12, 24 months. The crown of the tooth was divided into 9 equal squares and 6 classes of fracture types were created. Complications and their frequencies were evaluated based on the post-traumatic substance losses in these illustrated fracture types. Results: The incidence of complications was 28.9% at 6 months, 51.3% at 1year, and 63.9% at 2years. Class4 fractures had the highest probability of complications (32.4%) and the development of pulp necrosis (40.3%). It was detected that the complications such as pulp necrosis (21.6%) can be frequently observed in the 2nd year or later periods of crown fractures. Conclusion: In addition to current regular checks, periodic follow-up of crown fracture should be extended to reflect current findings. Dentists, patients, and their parents must be made conscious of the importance of the treatment and follow-ups of crown fracture.